Safety and efficacy of surgical fixation of fibula fractures using an intramedullary nail: a retrospective observational cohort study in 30 patients - Guilherme Boni; Gustavo Tadeu Sanchez; Gustavo Gonçalves Arliani; Boris A. Zelle; Robinson Esteves Santos Pires; Fernando Baldy dos Reis (2019)
Abstract Background Open reduction and internal fixation remains the standard treatment for displaced unstable ankle fractures. Plate fixation represents the most frequently used instrumentation option in fibula fractures and favourable outcomes have been reported. Recently, intramedullary nailing techniques have been suggested as a viable alternative resulting in less soft tissue disruption. The objectives of this study are to describe the surgical technique and to evaluate the safety and efficacy of using an intramedullary nail in patients undergoing surgical fixation of their fibula fracture. Methods A total of 30 skeletally mature patients with unstable ankle fracture who underwent intramedullary fixation of their fibula fractures from February 2016 to July 2017 were included in this retrospective study. Patients were evaluated using the Short Form-36 (SF-36) and the American Orthopaedic Foot and Ankle Society (AOFAS) at 18 months after surgery. Results All patients went on to fracture union. Two patients required a secondary surgical procedure. No patient included in this series developed any wound complications. The mean Physical Component Summary (PCS) of the SF-36 was 53.90 ± 13.3 and the mean Mental Component Summary Score (MCS) was 52.63 ± 11.12. The AOFAS subscale scores were 34.67 ± 1.03 for pain, 42.40 ± 0.2997 for function and 9.50 ± 0.2785 for alignment. Conclusions Our study demonstrates promising outcomes associated with intramedullary nail fixation of unstable fibula fractures. We recommend intramedullary nail fixation of fibula fractures to be a safe procedure with a low complication rate. Level of evidence Level 4 retrospective case series.